Fixed Point Theorems for \(α\)-\(ψ\)-Contractive Mappings of Integral Type in \(C^*\)-algebra Valued~Metric Space - Neetu,; Kumar, Manoj (Communications in Mathematics and Applications, 2024)
In this paper, we introduce two classes of generalized \(α\)-\(ψ\)-contractive type mappings of integral type and analyze the existence of fixed point for these mapping in \(C^*\)-algebra valued metric space. Our study extends and generalizes the result of several studies in the literature.
Keywords: Fixed point; α-ψ contractive mappings of integral type; C∗-algebra valued metric space